Actual and Potential Trade Agreements in the Asia-Pacific Estimated Effects - Ferrantino, Michael Joseph (World Bank E-Library Archive, 2020)
This paper assesses and compares the economic impacts of four actual and potential free trade agreements in the Asia-Pacific Region: the Comprehensive and Progressive Agreement for Trans-Pacific Partnership, the original Trans Pacific Partnership, the Regional Comprehensive Economic Partnership, and the Free Trade Area of the Asia-Pacific. Free trade areas with a larger scale and wider membership are expected to produce higher aggregate gains in increased gross domestic product and trade flows. U.S. withdrawal from the original Trans-Pacific Partnership reduced estimated gross domestic product gains for the Comprehensive and Progressive Agreement for Trans-Pacific Partnership countries by about half. For countries belonging to the Comprehensive and Progressive Agreement for Trans-Pacific Partnership and also negotiating the Regional Comprehensive Economic Partnership, the potential gains from an agreement with China and the Republic of Korea are substantial, but not as large as if the United States were to rejoin the original Trans-Pacific Partnership. On a sectoral basis, significant structural shifts are observed for food processing, wearing apparel, textiles, and transport equipment